The impact of Covid-19 pandemic on modification of medical teaching in Italy: A narrative review - Antonio Brusini (Wolters Kluwer Medknow Publications, 2023)
During the first wave of Covid-19 in Italy, there was a problem with University. Universities couldn't do face-to-face (FTF) lessons and started to do online lessons (OL). This study investigates the impressions of students, teachers, and institutions during the first wave situation. A search was conducted on the main international databases, and only studies conducted in Italy starting during the Covid-19 pandemic are considered. 9 studies tell about the impressions of students about OL lessons, and 10 studies speak about medical resident's situation and teacher's impressions. Studies about students give conflicting results, teachers are generally satisfied with the contents, but agree on the difficulty of not having relationships with students. Medical residents have reduced significantly the clinical and surgical practice, sometimes increasing the research. In the future, it is indispensable to create a system that guarantees the efficacy of FTF lessons for practice, it is still low in sanitary and medical courses in Italy during the pandemic period.